2003
DOI: 10.1046/j.1365-277x.2003.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Child malnutrition in Vietnam and its transition in an era of economic growth

Abstract: Children of rural households, poor households, and ethnic minority backgrounds are significantly more likely to be malnourished than urban residents, children of nonpoor households, and the majority Kinh population. Additionally, avenues to escape malnourishment are limited in the former categories. These results suggest that economic improvements in Vietnam have, for the most part, bypassed the rural poor and minorities, and targeting economic resources towards these groups will be most critical to reduce mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 10 publications
4
39
0
Order By: Relevance
“…The (a) lower rate weight increments and (b) similar rate height increments lead to the lower BMI and higher prevalence of underweight among the rural 2-9 year-olds. Our study results were consistent with those of Thang and Popkin (2003a) when comparing the children involved in both the Living Standard Surveys in 1992 and 1998 (i.e., there was a higher prevalence and a lower underweight reduction rate (low weight for age) and stunting (low height for age), a lower rate of escape and a higher rate of becoming undernourished among the rural residents and poor 6-11 yearolds) (Thang and Popkin, 2003a). Second, an explanation for the poorer nutrition status among the urban 2-9 year-olds in 1992 is that they were born in the years between 1982 and 1990.…”
Section: Discussionsupporting
confidence: 93%
“…The (a) lower rate weight increments and (b) similar rate height increments lead to the lower BMI and higher prevalence of underweight among the rural 2-9 year-olds. Our study results were consistent with those of Thang and Popkin (2003a) when comparing the children involved in both the Living Standard Surveys in 1992 and 1998 (i.e., there was a higher prevalence and a lower underweight reduction rate (low weight for age) and stunting (low height for age), a lower rate of escape and a higher rate of becoming undernourished among the rural residents and poor 6-11 yearolds) (Thang and Popkin, 2003a). Second, an explanation for the poorer nutrition status among the urban 2-9 year-olds in 1992 is that they were born in the years between 1982 and 1990.…”
Section: Discussionsupporting
confidence: 93%
“…Peru undergoes epidemiological and nutritional transition (Chaparro and Estrada 2012; Huicho et al 2009), with growing prevalence of childhood overweight and obesity whilst still hosting chronic malnutrition rates of 25% (Alvarez-Dongo et al 2012;Loret de Mola et al 2014;Pajuelo-Ramirez et al 2013). In Vietnam, the nutritional status of children has also changed: between 1992-93 and 1997-98 the prevalence of underweight decreased from 70% to 64%; and prevalence of overweight and obesity is 20% in school-aged children (Nguyen et al 2013;Thang and Popkin 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[6] Several studies have shown a clear correlation between iron deficiency anemia (IDA) and a series of determinants such as age of the child, [7] a high number of coinhabitants, [8] low per capita family income, [9] poor general socioeconomic conditions, [10] breast feeding pattern, [11] and worm infections. [2] The present study investigates the area-specific prevalence and determining factors of anemia and malnutrition among children of Albasra village, one of the Egyptian villages, to produce directives for a management program that can be directed at populations with similar characteristics.…”
Section: Introductionmentioning
confidence: 99%